DDVP (Shell Dichlorvos) for pregnant sows - Koch, B.A.; Cowman, G.L.; Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Recent laboratory and research station reports have indicated that 2,2-dichlorovinyl dimethyl phosphate (DDVP) (Shell Dichlorvos) fed to pregnant sows late in gestation may have a favorable effect on the newborn pigs. This study was designed to attempt to measure that effect in terms of increased production or improved efficiency in a commercial herd. The commercial swine herd of Arnold and Bob Rose (Cawker City, Kansas) was used in this study which was financed by the Shell Chemical Company. The Rose herd is one of the larger outstanding commercial pork producing units in Kansas. For all practical purposes it is an S.P.F. herd although S.P.F certification has not been maintained.
Swine Industry Day 1968 is known as Swine Day, 1968
Keywords: Swine; DDVP (Shell Dichlorvos); Pregnant sows